Предмет:
МатематикаАвтор:
анонимcos^2a + sin^2a = 1;
sin2a = 2 * sina * cosa;
cos2a = cos^2a - sin^2a;
1 - cos2x / sin2x = (1 - cos^2x + sin^2x) / 2 * sinx * cosx =
= (cos^2x + sin^2x - cos^2x + sin^2x) / 2 * sinx * cosx =
= sinx / cosx = tgx.
Ответ: 1 - cos2x / sin2x = tgx.
Автор:
cocoamccoyДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть